Study of Craniofacial Relations and Facial Types in Greek Population with Normal Occlusion - Sidiropoulou S. (Balkan Stomatological Society, 2015)
The purpose of this study was to determine the range of certain skeletal structures and investigate their relationship and facial types in Greeks with normal occlusion. 123 lateral cephalometric radiographs obtained from 65 males and 58 females (mean age: 24 and 23 years respectively) with normal occlusion were studied at the Dental School of Aristotle University of Thessaloniki. Angles SNA, SNB, NL-NSL, ML-NSL, NSBa and ML-NL were measured and analysed.